2011
DOI: 10.4103/1119-3077.84027
|View full text |Cite
|
Sign up to set email alerts
|

Neck masses in children: Etiopathology in a tertiary center

Abstract: Many neck masses in otherwise healthy children in our setting were malignant. We advocate early surgical consultation and thorough histopathologic analysis of neck masses in children in our subregion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 16 publications
18
18
0
Order By: Relevance
“…In line with our results, many other studies have reported that inflammatory lesions have the highest frequency among the head and neck masses in children; this frequency varied from 43.9% in the study by Lucumay (12) to 58% in the study by Al-Mayoof (13). However, some studies have reported that (15). In our study, inflammatory/reactive/infectious lesions showed a significantly higher frequency in males (2:1).…”
Section: Discussionsupporting
confidence: 90%
“…In line with our results, many other studies have reported that inflammatory lesions have the highest frequency among the head and neck masses in children; this frequency varied from 43.9% in the study by Lucumay (12) to 58% in the study by Al-Mayoof (13). However, some studies have reported that (15). In our study, inflammatory/reactive/infectious lesions showed a significantly higher frequency in males (2:1).…”
Section: Discussionsupporting
confidence: 90%
“…Our study findings were similar to Showkat et al 8 Lucumay et al and Osifo et al reported a lower incidence which could be due to different demographic distribution of study population in these studies. 9,13 We had 23 cases (15.3%) of thyroglossal cyst in our study. All patients had slowly growing painless neck masses mostly in midline or anterior triangle of neck.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 It is a cause for anxiety as chances of malignancy are there. 3 Etiology is divided into three groups-inflammatory or infectious, abnormal embryonic development and neoplastic. 4 Fortunately benign masses are more frequently encountered which are reaction to the upper airway infection.…”
Section: Introductionmentioning
confidence: 99%
“…The causes of acute pediatric neck masses are highly variable and include infectious, congenital, inflammatory, and neoplastic lesions . The clinical approach to this broad differential diagnosis is complicated by the fact that approximately half of young children have palpable normal cervical lymph nodes, whereas parental anxiety often focuses on possible malignancy …”
mentioning
confidence: 99%
“…2 The clinical approach to this broad differential diagnosis is complicated by the fact that approximately half of young children have palpable normal cervical lymph nodes, 3 whereas parental anxiety often focuses on possible malignancy. 4 Although the history and physical examination are crucial diagnostic steps, children presenting to the PED with neck masses may have worrisome clinical features (eg, fever, neck stiffness, and rapid mass expansion) that trigger emergency physicians to perform laboratory and imaging investigations. Unfortunately, there are no published evidence-based guidelines for investigations of this cohort in the PED.…”
mentioning
confidence: 99%